Friction stir processing of boron carbide reinforced aluminium surface (Al-B4C) composite: Mechanical characteristics analysis. (2022) - Boopathi, Sampath; Thillaivanan, Alagu; Pandian, M.; Subbiah, Ram; Shanmugam, P.
Abstract: In this article, the boron carbide reinforced Aluminium alloy surface composite material was fabricated through the friction-stir processing method. The Al6061 alloy and B4C particles were used as matrix and reinforced materials respectively. The influences of volume percentage of boron-carbide, traveling feed rate, and rotational speed on tensile strength and wear were investigated using the L9 Taguchi technique. The moderate rotating speed and traveling speed of the tool have been preferred to attain optimum responses. The highest tensile strength of 347 MPa and minimum wear of 55 µm were obtained from 15% of the volume of boron carbide particles, 1400 rpm of rotating speed, and 40 mm/min traveling speed of the tool. The optimum Al6061-B4C surface composites micro-structure has also been studied through scanning electron microscope images.